Building 21st-century skills through the recent behavioral learning for students outcome - Putri, Dinda Karunia; Zainovi, Putri Sarah; Hanip, Singgih Aulia; Wiryanto, Wiryanto; Julianto, Julianto (Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to explore the implementation of behavioristic learning theory in the context of 21st-century basic education in Indonesia. This study uses the Systematic Literature Review (SLR) method to understand how behavioristic principles can be integrated into modern teaching practice from 10 reputable journals (Scopus and Sinta), the research stages included planning, conducting, and reporting. Research result in this study suggests that the implementation of behavioristic theory requires a good classroom environment and the use of reward and punishment schemes to shape student behavior. Teachers are expected to be actively involved in the learning process, provide constructive criticism, and conduct an initial analysis of students' ability to design appropriate lesson plans. This research offers novelty in integrating behavioristic theory into modern basic education in Indonesia and makes practical contributions for teachers and implications for the education system to achieve national education goals. This research supports developing quality and sustainable human resources towards a Golden Indonesia 2045.